The Effectiveness of Nature-Based Person-Centred Group Counselling in Improving Spiritual Well-being Among Elderly - Haruns, Khadijah Hanina; Saraswati, Sinta; Sugiharto, Dwi Yuwono Puji (Bulletin of Counseling and Psychotherapy, 2025)
Aging brings not only physical decline but also psychological and spiritual challenges, particularly among elderly individuals living in communal environments such as Islamic boarding houses (pesantren). While pesantren settings offer religious routines and social support, structured psychological interventions tailored to older people’s spiritual needs are limited. This study examines the effectiveness of nature-based, person-centred group counselling in improving the spiritual well-being of elderly residents at Pesantren Rhoodiyatam Mardhiyyah, Semarang. Using a sequential explanatory mixed-methods design, the research involved a quantitative phase followed by qualitative exploration. The quantitative phase employed a one-factor pretest-multiple posttest control group design analysed using Mixed ANOVA, while the qualitative phase used thematic analysis based on in-depth interviews. A total of 14 participants aged 60 and above were purposively selected. Mixed ANOVA results revealed significant main effects of the intervention across time (p < .001) and between groups (p < .001), with strong interaction effects (ηp² = 0.855), indicating that the nature-based group counselling significantly enhanced spiritual well-being across personal, communal, environmental, and transcendental dimensions. The thematic analysis supported these findings, with participants reporting increased inner peace, emotional openness, social connectedness, and deeper spiritual reflection. Nature-based person-centred counselling provides a practical and culturally relevant intervention to enhance the spiritual well-being of elderly individuals in Islamic boarding schools. This approach integrates therapeutic engagement with nature, group support, and spiritual reflection, offering valuable implications for elderly care programs in religious settings.